2017
DOI: 10.3988/jcn.2017.13.1.62
|View full text |Cite
|
Sign up to set email alerts
|

SCN1A Gene Mutation and Adaptive Functioning in 18 Vietnamese Children with Dravet Syndrome

Abstract: Background and PurposeDravet syndrome is a rare and severe type of epilepsy in infants. The heterogeneity in the overall intellectual disability that these patients suffer from has been attributed to differences in genetic background and epilepsy severity.MethodsEighteen Vietnamese children diagnosed with Dravet syndrome were included in this study. SCN1A variants were screened by direct sequencing and multiplex ligation-dependent probe amplification. Adaptive functioning was assessed in all patients using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Additionally, we administered the VABS test which, unlike other IQ or DQ tests, allows comparison of adaptive daily functions at different ages, irrespective of developmental level and cooperation. VABS has previously been used in two studies assessing cognition and behavior in children with Dravet [48, 49]. This type of assessment suggested a distinctive profile for these children, with higher scores on the socialization domain, as compared to communication or living skills.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we administered the VABS test which, unlike other IQ or DQ tests, allows comparison of adaptive daily functions at different ages, irrespective of developmental level and cooperation. VABS has previously been used in two studies assessing cognition and behavior in children with Dravet [48, 49]. This type of assessment suggested a distinctive profile for these children, with higher scores on the socialization domain, as compared to communication or living skills.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is not surprising that, in addition to seizures, patients also have slowing of cognitive development and gait problems. 2,7 Relative to the pediatric population, there is limited information about DS in adults. [8][9][10][11][12] The majority of patients continue to have refractory seizures as adults, although their convulsive seizures can be restricted to sleep periods.…”
mentioning
confidence: 99%
“…As such, it is not surprising that, in addition to seizures, patients also have slowing of cognitive development and gait problems. 2,7…”
mentioning
confidence: 99%
“…[1,2,6] We screened 48 DS patients and found 26 DS patients (54.2%) had SCN1A variants (Table S1), which were also reported in previous studies and database. [3032] Studies reported causative variants of SCN1B p.R125C in two infants with DS [8,10] and SCN1B p.lle106Phe in one of 67 DS patients. [9] In order to find the pathogenesis of DS except SCN1A variants, we carried out this study to investigate the variants of SCN1B and SCN2B variants in DS patients.…”
Section: Discussionmentioning
confidence: 99%